STUDY OF FUTURE PRIMARY SCHOOL TEACHERS’ CULTURAL TRAINING WITHIN THE INFORMATION CULTURE OF SOCIETY - Vinnyk, Т.О. (Journal of Information Technologies in Education (ITE), 2016)
The article presents the results of scientific studies and experimental approbation of pedagogical conditions of future primary school teachers’ cultural training taking into account the information culture of society. The nature and structure of the notion «future primary school teachers’ cultural training» are clarified. The indicated phenomenon is considered as the structure of four levels, the core of which is personality’s humanistic orientation, the totality of psychological-pedagogical and cultural knowledge and skills, the complex of professionally significant personal qualities. The author pointed out the criteria and related indicators of cultural proficiency, they are: value-motivational (vocational and humanistic orientation; the presence of values and professional motives; motivation for success); substantial and procedural (knowledge and skills in psycho-pedagogical disciplines; the body of knowledge regarding the content and components of cultural training, cultural skills); assessment and behavioral (the existence of communicative qualities, ability to empathy, tolerance). Levels of future primary school teachers’ cultural readiness: high, average and low are characterized. The experience of ICT using in students’ cultural training is presented. Pedagogical conditions of future primary school teachers’ cultural training in University are identified, their effectiveness is proved by experimental testing.